Mechanical properties of concrete containing sawdust as partial sand replacement - Siti Nazila, Mohammad Udin (2017)
The rising costs of building construction in developing countries have been a source of concern to government and private developers due to high demand in concrete materials among the construction sectors. The most critical material used in making concrete is fine aggregate. Due to high demand of the sand, the excessive sand mining had occur and give negative impact to the environment. Therefore, in order to reduce the impact on environment, an alternative of materials that can be replaced the sand in concrete is sawdust. Sawdust becomes the most abundant and inexpensive waste material resulted from the timber industry. Currently, timber industry has become the major contributor to Malaysia’s economy. Waste materials from the industry are disposed in sanitary landfills and open dumped in uncontrolled handling. This issue also led to environment problem in the country. So, an experimental study considered the use of sawdust as substitute in fine aggregate in the production of concrete is carried out. It investigates the properties of concrete which is workability, compressive strength, flexural strength and water absorption. The concrete is casted by replacing sand with 2%, 4%, 6%, 8% and 10% of sawdust. Concrete cube measuring 100 x 100 x 100mm and beam measuring 100 x 100 x 500mm were casted and their strength evaluated at 7, 14 and 28 days. Increase in percentage of sawdust in concrete cubes led to a corresponding reduction in compressive strength values as well as flexural strength values. Meanwhile, from the result, the water absorption gradually increase as the sawdust content increase.